Fibromyalgia Syndrome - Choy, Ernest ([Oxford] : Oxford University Press, 2015)
This succinct and practical pocketbook provides clinicians with an essential understanding of the pathophysiology of pain in fibromyalgia, as well as a guide to the diagnosis and management of this chronic condition.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 1, 2015).
Keywords: Fibromyalgia